Birth characteristics and all-cause mortality: a sibling analysis using the Uppsala birth cohort multigenerational study. (3rd May 2016) - Juárez, S.; Goodman, A.; De Stavola, B.; Koupil, I.
Abstract : This paper investigates the association between perinatal health and all-cause mortality for specific age intervals, assessing the contribution of maternal socioeconomic characteristics and the presence of maternal-level confounding. Our study is based on a cohort of 12, 564 singletons born between 1915 and 1929 at the Uppsala University Hospital. We fitted Cox regression models to estimate age-varying hazard ratios of all-cause mortality for absolute and relative birth weight and for gestational age. We found that associations with mortality vary by age and according to the measure under scrutiny, with effects being concentrated in infancy, childhood or early adult life. For example, the effect of low birth weight was greatest in the first year of life and then continued up to 44 years of age (HR between 2.82 and 1.51). These associations were confirmed in within-family analyses, which provided no evidence of residual confounding by maternal characteristics. Our findings support the interpretation that policies oriented towards improving population health should invest in birth outcomes and hence in maternal health.